Paddy Clarke, ha-ha-ha - Doyle, Roddy, 1958- (Penguin Books, 1995)
"In this national bestseller and winner of the Booker Prize, Roddy Doyle, author of the 'Barrytown Trilogy,' takes us to a new level of emotional richness with the story of ten-year-old Padraic Clarke. Witty and poignant--and adored by critics and readers alike--Paddy Clarke Ha Ha Ha charts the triumphs, indignities, and bewilderment of Paddy as he tries to make sense of his changing world."--Publisher's description.